ANALISIS DALAM PEMBERIAN KREDIT OLEH LEMBAGA PERBANKAN DALAM PERSPEKTIF PRECAUTIONARY BANKING PRINCIPLE - Dwitayani, Ni Made Ayu Rusmega; Utami, Putu Devi Yustisia (Kertha Desa, 2024)
Penelitian ini dilakukan dengan tujuan untuk mengetahui pengaturan precautionary banking principle dalam hukum positif di Indonesia dan upaya yang dilakukan oleh bank dalam melakukan analisis dalam pemberian kredit guna mencegah timbulnya risiko kredit bermasalah. Riset dilakukan dengan menggunakan metode normative. Ditemukan bahwa Regulasi yang mengatur mengenai Precautionary Banking Principle yakni UU Perbankan, UU Pengembangan dan Penguatan Sektor Keuangan, PBI dan POJK. Upaya yang dilakukan oleh pihak lembaga perbankan untuk mencegah terjadinya risiko kredit bermasalah dengan mengacu pada prinsip 5C yaitu character, capacity, capital, collateral dan condition of economy. Dengan selalu adanya pengawasan yang cermat dengan diterapkannya precautionary banking principle di dalam lembaga perbankan guna mencegah timbulnya risiko kredit bermasalah. This research was conducted with the aim of knowing the analysis in the provision of credit by banking institutions in the perspective of precautionary banking principle. In this case to prevent the risk of problem loans. The design of the two main issues discussed in this case is how to regulate the precautionary banking principle in positive law in Indonesia and what are the efforts made by banks in conducting analysis in granting credit in order to prevent the risk of non-performing loans. The research was carried out using normative methods It was found that the regulations governing the Precautionary Banking Principle are the Banking Law, the Financial Sector Development and Strengthening Law, PBI and POJK. Efforts made by banking institutions to prevent the risk of problem loans by referring to the 5C principles, namely character, capacity, capital, collateral and conditions of economy. By always having careful supervision by applying the precautionary banking principle in banking institutions to prevent the risk of problem loans.